Oncological outcome after radical prostatectomy: Marital status does not make a difference. (17th March 2015) - Schiffmann, Jonas; Beyer, Burkhard; Tennstedt, Pierre; Boehm, Katharina; Mehring, Gisa; Schlomm, Thorsten; Salomon, Georg; Karakiewicz, Pierre; Graefen, Markus
<x xml:space="preserve">Abstract</x> Objectives To examine the impact of marital status on prostate cancer characteristics at radical prostatectomy and oncological outcome after surgery at a high‐volume center. Methods We relied on the Martini‐Clinic Prostate Cancer database and investigated 8088 prostate cancer patients treated with radical prostatectomy between January 2000 and March 2011. We analyzed differences in clinical and pathological characteristics according to marital status (married and partnership vs single). Additionally, we relied on multivariable Cox regression analyses to predict biochemical recurrence, metastases and death after radical prostatectomy. Finally, Kaplan–Meier analyses were used in a propensity score‐matched cohort, adjusted for clinical and pathological characteristics, to examine differences in biochemical recurrence‐free, metastases‐free and overall survival according to marital status. Results According to marital status, no significant differences were recorded within clinical and pathological characteristics (all P > 0.05). The impact of marital status on biochemical recurrence (hazard ratio 1.0, 95% confidence interval 0.9–1.3, P = 0.7), metastases (hazard ratio 1.3, 95% confidence interval 0.8–2.1, P = 0.3) and death (hazard ratio 0.8, 95% confidence interval 0.4–1.6, P = 0.6) after radical prostatectomy was not significant (median follow up 48 months). Kaplan–Meier analyses recorded no significant differences for biochemical recurrence‐free, metastases‐free and overall survival (all log–rank P > 0.05) according to marital status. Conclusions Marital status does not affect the clinical and pathological characteristics of radical prostatectomy patients treated at a high‐volume center. Furthermore, marital status does not affect biochemical recurrence‐free and metastases‐free survival after radical prostatectomy.